Beezdigital Business Development Strategy with Analysis of Business Model Canvas - Sari, Dwi Widiya; Wibowo, Januar; Candraningrat, Candraningrat; Fianto, Achmad Yanu Alif (International Conference On Economics Business Management And Accounting (ICOEMA), 2022)
In an effort to support the progress of MSMEs in Indonesia, Beezdigital conducts research on its business model. This research is used to identify strategies, vulnerabilities, and opportunities in Beezdigital business development through analysis using the Business Model Canvas method. This study uses a descriptive qualitative research method, by analyzing the business model using the Business Model Canvas, which includes customer segments, value propositions, channels, customer relationships, revenue streams. ), main activity, main resource, main partner, and cost structure. This research was conducted from April 2022 to July 2022 at the Beezdigital Creative Agency. Meanwhile, based on the findings of the researchers, it was concluded that in the implementation of the business model canvas strategy, every element of the planning implementation that had been prepared had gone well according to the plan, it was just that there were obstacles. in several segments implemented, among others: customer segments, main activities, key resources, and key partners. From the analysis carried out, Beezdigital can formulate an update strategy that must be carried out.